Selective internal radiation therapy in treatment of hepatocellular carcinoma: new concepts of personalization. (July 2016) - Abraham, Jella-Andrea; Yeghiazaryan, Kristina; Golubnitschaja, Olga
Hepatocellular carcinoma (HCC) is a global health problem, with more than half a million new cases diagnosed annually and mortality rates at similar level. The majority of HCC is diagnosed at intermediate–advanced stages being, therefore, an issue for palliative rather than curative care. Selective internal radiation therapy (SIRT) is one of the best appropriate palliative treatment modalities in HCC management. Although delivering satisfactory results, SIRT application comes along with frequent complications and tumor recurrence. Recent studies suggest treatment algorithm tailored to the person as improving individual outcomes and reducing treatment-related complications. This review provides insights to implicate innovative concepts of predictive, preventive and personalized medicine in SIRT application to HCC cohorts.